Development of augmented reality in the basic physics practicum module. (April 2020) - Firmansyah, J; Suhandi, A; Setiawan, A; Permanasari, A
Abstract: This research aims to design and develop a media lab in the form of Augmented Reality applications that are used in basic physics lab module. AR applications work with a tracking system and the reconstruction of the 2D marker contained in the experimental module to display 3D video animation. The method used in this research is the development of software includes the stages of collecting and analyzing the needs, do the design and manufacturing applications, validation and testing by the user, and revision. Results of the assessment by the AR application validator media and materials are respectively 80% and 85% in the predicate is valid and may be used after minor revisions. The results of trials by students as the user indicates that the 2D marker on lab module was initially less obvious and less sensitive at the time of scanning. However, after the revision of the 2D marker on lab module, 2D AR marker was sufficiently clear and sensitive at the time of scanning so that AR can help the general practical implementation and the AR content to support the practical implementation. The results showed that the development of AR applications had been successfully carried out and the AR application can function well with the scan time 1-1.5 second at a distance of 10-20 cm and successfully used in the experimental module at an angle of <90 0, with the result that, AR applications in basic physics practicum module as the media are supporting practicum implementation